Why Pictures? From Art History to Business History and Back Again. Issue 1 (2nd January 2020) - Edwards, Steve
Abstract : Photographic history took root in the discipline of art history with its focus on pictures, and subsequent critical histories have largely retained this image-centred focus. Yet there is no inherent reason why the study of photography needed to become a history of pictures especially, as in some respects the images might not be the most important aspect of the practice. In recent years there has been a flurry of studies examining aspects of photographic industry and business arrangements. In this article I present some debates from the field of academic business history, which raise issues of relevance for historians of photography. Reese V. Jenkins's influential study of Kodak, Image and Enterprise (1975), provides the opportunity for investigating some of these issues. A short conclusion on the English daguerreotype trade provides an illustration or coda to these themes.